PENINGKATAN KOMPETENSI PENDIDIK PADA JENJANG PENDIDIKAN ANAK USIA DINI - Laily Hidayati (LPPM Institut Agama Islam Al-Hikmah Tuban, 2015)
In several studies on the important role of educators or teachers in the process of socialization and development of the child, Good & Brophy, 2007; Linney & Seidman, 1989 stated that,